ANALISIS KINERJA ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA PEMERINTAH DAERAH KABUPATEN PULAU MOROTAI TAHUN ANGGARAN 2013 - 2015 - Alfred Labi (Universitas Widyatama, 2019)
The purpose of this study is to determine the performance of the Revenue and Expenditure Budget Region (APBD) at the Regional Government of Pulau Morotai Regency Budget Year 2013-2015. As the output target is expected this research can also be published in national scientific journals and can be used as teaching materials in the lecture process. The form of this research is quantitative research conducted in the Regional Government of Morotai Island District. Data collection technique is done by interview, observation and other supporting documentation relevant to this research. To measure the performance of the budget (APBD) Morotai Island used the method of analysis by using the ratio of Regional Financial Independence, Effectiveness Ratio Against PAD, Regional Financial Efficiency Ratio, Harmony Ratio, Growth Ratio, and Ratio Proportion of APBD. Findings in research on the performance of Regional Revenue and Expenditure Budget (APBD) in Morotai Island District Government Fiscal Year 2013-2015 Where the performance of local government in carrying out its duties in the region is supported by the availability of Budget in the form of Regional Budget (APBD) . Thus, the higher budget absorption of various local government programs, the better the performance of the respective governments.